Los vasos-efigie antropomorfos: un ejemplo de la orfebrería de la costa central durante el Periodo Intermedio Tardío y el Horizonte Tardío - Carcedo, Paloma (Pontificia Universidad Católica del Perú, 2012)
Anthropomorphic Effigy Vases: A Silvermith’s Production during the Late Intermediate Period and Late HorizonAnthropomorphic effigy vases have been classified, without any scientific basis, as belonging to the Chimu Culture. This investigation shows how these kinds of vases are more related in iconography as well as in provenance with the iconography of the central coast of Peru. In a selection of nine vases analysed, we determine different techniques of manufacture, which indicate the high technological complexity achieved by the precolumbian metal smiths during the Late Intermediate period and the Late Horizon. This study seeks to clarify, with the help of historic and ethnographic documentation, the social importance of the silversmith’s workshops that elaborated the effigy vases in question. We hope through the study of these archaeological remains and their comparison with historical texts, to decipher the symbolic and ritual value, as well as possible religious influences in their manufacture along the Peruvian coast. Finally, the possible process used by the coastal metal smiths in the manufacture of the effigy vases was identified by means of electronic microscope and metalographic analysis.